PENGARUH AGENSI HAYATI TERHADAP TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Rusdiana, Yayun Farikha; Munambar, Siwitri (Jurnal Ilmu-Ilmu Pertanian, 2019)
Biological agents as one of the alternatives that are environmentally friendly control and in accordance with the guidelines of IPM is still not implemented. The purpose of this study to determine the interaction of dose and concentration of biological agents on the growth and yield of onion as well as to the intensity of the disease on onion crop, effect of the use of biological agents Trichoderma sp on growth, onion, and diseases of the onion crop, the concentration of PGPR right for growth and onion as well as against diseases of the onion crop. Fieldwork was arranged in a randomized block design Complete (RAKL) two factors, one control and three replications. The irst factor is the dose of Trichoderma harsianum (T) consists of two levels ie: T0: Without Trichoderma harsianum L, T1: Trichoderma harsianum L. dose of 50 kg / ha (5 mg / m2). The second factor is the concentration of PGPR (P) consists of 4 levels: P0: Without PGPR, P1: PGPR concentration of 2%, Q2: PGPR concentration of 4%, P3: PGPR concentration of 6%. The results showed no interaction between dose and concentration on the intensity of fusarium wilt, growth variables dry weight per hill, tuber crops variable dry weight per hectare. The highest efficacy for controlling diseases in onion combination treatment without the use of Trichoderma sp and PGPR concentration of 0%. PGPR concentration of 6% gave the highest yield of the dry weight of tuber crop yield of 12.7 tonnes per hectare.